Surface Display Technologies for Whole-Cell Biocatalysts: Advances in Optimization Strategies, Food Applications, and Future Perspectives - Baoyu Zhang; Xing Gao; Yu Zhou; Shengping You; Wei Qi; Mengfan Wang (Foods)
Surface display technology has revolutionized whole-cell biocatalysis by enabling efficient enzyme immobilization on microbial cell surfaces. Compared with traditional enzyme immobilization, this technology has the advantages of high enzyme activity, mild process, simple operation and low cost, which thus has been widely studied and applied in various fields. This review explores the principles, optimization strategies, applications in the food industry, and future prospects. We summarize the membrane and anchor protein structures of common host cells (Escherichia coli, Bacillus subtilis, and yeast) and discuss cutting-edge optimization approaches, including host strain genetic engineering, rational design of anchor proteins, innovative linker peptide engineering, and precise regulation of signal peptides and promoters, to maximize surface display efficiency. Additionally, we also explore its diverse applications in food processing and manufacturing, additive synthesis, food safety, and other food-related industries (such as animal feed and PET packaging degradation), demonstrating their potential to address key challenges in the food industry. This work bridges fundamental research and industrial applications, offering valuable insights for advancing agricultural and food chemistry.